Ammonium redox-responsive receptors containing two or three ferrocene redox-active centres attached to di- and tri-aza crown ether macrocycles - Beer, P; Crowe, D; Main, B (1989)
The binding of NH4+ to novel ferrocenyl aza crown ethers 7 and 6, respectively, containing two and three ferrocene redox-active centres attached to amine functionalised di- and tri-aza crown ether macrocycles, results in large anodic shifts of the ferrocene/ferricinium redox couple, by up to 220 mV with 6. © 1989.